ChemInform Abstract: Hydride Reduction by a Sodium Hydride—Iodide Composite. Issue 28 (June 2016) - Too, Pei Chui; Chan, Guo Hao; Tnay, Ya Lin; Hirao, Hajime; Chiba, Shunsuke
Abstract: Reduction of nitriles, amides, and imines is achieved using NaH in the presence of LiI or NaI.